2011
DOI: 10.1021/la201829y
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis and Structural Control of PtSn Bimetallic Nanoparticles

Abstract: PtSn bimetallic nanoparticles with different particle sizes (1-9 nm), metal compositions (Sn content of 10-80 mol %), and organic capping agents (e.g., amine, thiol, carboxylic acid and polymer) were synthesized by colloidal chemistry methods. Transmission electron microscopy (TEM) measurements show that, depending on the particle size, the as-prepared bimetallic nanocrystals have quasi-spherical or faceted shapes. Energy-dispersive X-ray (EDX) analyses indicate that for all samples the signals of both Pt and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 72 publications
3
52
1
Order By: Relevance
“…2.5 nm. Wang et al 37 have reported such bimetallic PtSn nanowires previously. 38 The diameter of PtSn spheres in the present study matches the width of nanowires suggesting the PtSn nanowires result from spherical particles forming chains.…”
Section: Resultsmentioning
confidence: 99%
“…2.5 nm. Wang et al 37 have reported such bimetallic PtSn nanowires previously. 38 The diameter of PtSn spheres in the present study matches the width of nanowires suggesting the PtSn nanowires result from spherical particles forming chains.…”
Section: Resultsmentioning
confidence: 99%
“…Bimetallic alloy nanocrystals can effectively reduce the consumption of noble-metals [12,15]. Although Pt is generally known to be one of the best electrocatalysts, it is high priced, has limited capability for CeC bond scission, and is vulnerable to poisoning by carbonaceous intermediates generated during the EOR process.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In this context,s trategies that enableo ne to maximize their performance become very important as noble metals are usually expensive and low in reserves. [7,8] Furthermore, bimetallic nanoparticles have proved to be novel materials with excellent catalytic properties, which can be used for differentr eactions, such as hydrogenation and oxidation. While their bimetallic compositions enable the combination/synergism of properties between the metal components, hollow interiors provide higher surface-to-volume ratios relative to their solid counterparts.…”
Section: Introductionmentioning
confidence: 99%